Increase in the volume of the breast implant by passing organic material into it - Milton Jaime Bortoluzzi Daniel; Leandro Alves Garcia Bortoluzzi Daniel; Vitor Alves Garcia Bortoluzzi Daniel; Lincoln Graça (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: The search for an anatomical substitute for the breast, for the purpose of correcting aesthetic problems has a long history of failure until the arrival of silicone. Since the beginning of its use, in the 1960s, many complications have appeared, such as infection, rejection, rupture, in addition to silicone leakage. We did not find in the literature, however, any report on the passage of materials from the human organism to the interior of implants. The objective is to identification by infrared spectrophotometry (FTIR) and clinical analysis, reporting the passage of organic substances into breast implants without any violation of their capsule. Methods: 1500 pairs of breast implants were analyzed, surgically removed from 1998 to 2018. Of which six were included in the study. Results: Three materials were analyzed showing macroscopic changes in their interior, without violating the capsule. A second sample was performed on a similar implant, but without use. The third material was a sample of fatty breast tissue removed from the patient during the surgery. Materials compatible with fat, animal protein and hemoglobin were found inside the implant. Conclusions: The change evidenced in the material inside the two implants indicates the occurrence of the passage of organic materials through an intact capsule.